IMPLEMENTASI METODE PEMBIASAAN UNTUK MENINGKATKAN KEDISIPLINAN SHOLAT DZUHUR BERJAMAAH SISWA DI MADRASAH TSANAWIYAH SOLEH AL- MUBAROK KEC. TUNGKAL ULU KAB. TANJUNG JABUNG BARAT PROVINSI JAMBI - Ria Ningsih, Bekti; Hindun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the problem of low student discipline in performing congregational Dhuhr prayer at Soleh Al-Mubarok Islamic Junior High School, Tungkal Ulu District, West Tanjung Jabung Regency, Jambi Province. The purpose of this study is to describe the implementation of the habituation method, to identify the supporting and inhibiting factors, and to examine its contribution to improving students’ discipline in performing congregational Dhuhr prayer. This research employed a qualitative descriptive approach. The participants consisted of the head of the madrasah, fiqh teachers, and students. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the habituation method was implemented in a structured and continuous manner through scheduled and compulsory congregational Dhuhr prayer activities under teachers’ supervision. The implementation of this method contributed positively to students’ prayer discipline, which was reflected in improved punctuality, higher participation, and better order during the prayer activities. However, several obstacles were identified, including limited student awareness and insufficient supervision. These challenges were addressed through continuous guidance, motivation, and regular evaluation by teachers and school administrators. Overall, the habituation method was found to be effective in strengthening students’ discipline in performing congregational Dhuhr prayer and in fostering positive religious habits within the school environment.